Non-Coding RNAs - Tutar, Lütfi; Aras, Sümer; Tutar, Esen (IntechOpen, 2020)
Noncoding RNAs (ncRNAs) are an attractive research field in the RNA world. ncRNAs play important roles in regulating gene expression in animals, plants, and various human diseases. It is clear that current and further research on ncRNAs will change our knowledge of the nature of genome composition by editing previous dogmas. This book provides an overview of current knowledge on ncRNA research by dealing with miRNA and ncRNA-related human diseases, plant miRNA markers, and the roles of lncRNAs in cancer and epigenetics.